DATA SOVEREIGNTY VS. OPEN INNOVATION: A LITERATURE REVIEW OF DIGITAL ECONOMY REGULATION IN THE ERA OF ARTIFICIAL INTELLIGENCE AND THE GREEN ECONOMY - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This article examines the structural tension between data sovereignty and open innovation in the regulation of the digital economy in the era of artificial intelligence (AI) and the green economy, using a systematic literature review approach. Data sovereignty, as enshrined in Indonesia’s Personal Data Protection Act (PDP), protects national strategic assets from exploitation by global platforms, yet hinders access to essential datasets for the development of AI models and green technology collaboration. Conversely, the open innovation paradigm, through regulatory sandboxes and open data policies, drives the digital economy target of Rp4,500 trillion (2030), but risks a brain drain of domestic data. A comparative analysis of the EU, US and China reveals a trade-off between protective regulation and market-driven approaches, whilst the Indonesian context demands a hybrid governance model: limited data localisation combined with trusted data-sharing frameworks. Recommendations include the 2026 Presidential Regulation on AI, strengthening cloud sovereignty, and a Digital Sovereignty Index to realise contextual AI that is sovereign, innovative, and sustainable, paving the way for Indonesia Emas 2045.